A79: Pulmonary Hemorrhage in Pediatric Systemic Lupus Erythematous: Clinical Course and Outcomes. Issue 11 (March 2014) - Singla, Saimun; Muscal, Eyal; Canter, Debra; DeGuzman, Marietta; Vece, Timothy
Abstract : Background/Purpose: Pulmonary hemorrhage (PH) is a rare and devastating manifestation of SLE, occurring in 1–5% of adult cohorts with mortality rates ranging from 70%‐90%. The majority of PH reported in SLE refers to the adult population, and there is a paucity of data in pediatrics. Therefore, we describe our experience with PH in pediatric SLE, outlining disease presentation, treatment, and outcomes. Methods: We reviewed records of pediatric SLE patients who presented with pulmonary involvement diagnosed between January 2000 and August 2010. Inclusion criteria included > 4 SLE classification criteria and PH based on pulmonary evaluation by BAL, lung biopsy and/or characteristic imaging with worsening anemia. We describe our pediatric cohort, presenting symptoms, diagnostic modalities, various interventions and overall outcomes. Results: Seven of 401 (1.7%) SLE patients met inclusion criteria for PH. Patients were predominantly male (71.4%) and Hispanic (57.1%). Median age of PH presentation was 13.5 years (range 2.0–15.2). Episodes were primarily within the first 3 months of SLE diagnosis (71.4%) and were a presenting manifestation for SLE in 28.6% of our patients. All patients presented with a new cough, dyspnea, hypoxemia, anemia and abnormal CXR. Hemoptysis was present in 28.6%. Four out of 6 children had chest CT findings with diffuse ground glass opacities (66.6%) and 3 with nodules (50%). Additional non‐pulmonary features included fever (71.4%), renal disease (57.1%), cytopenias (71.4%), cardiac disease (50.0%), and positive antiphospholipid antibodies (85.7%). Eighty‐five percent required supplemental oxygen and 57.1% required mechanical ventilation. Hemosiderin‐laden macrophages without infection were observed in 3 BAL's. Out of the two lung biopsies performed, both revealed diffuse hemorrhage and one demonstrated immunoglobulin and complement deposition. All were treated with pulse doses of methylprednisolone infusions. Other therapeutic interventions included cyclophosphamide (42.8%), plasma exchange (42.8%), rituximab (85.7%) and IVIG (14.2%). Survival rate was 87.5%. All patients were maintained on corticosteroids and 66.6% received monthly cyclophosphamide infusions. Subsequent outpatient therapies included IVIG (33.3%), azathioprine (16.6%) or rituximab (16.6%). No patients had recurrences of PH. No survivors required supplemental oxygen nor developed interstitial lung disease (median follow‐up 2.6 years, range 1.5–5.0). Conclusion: In our review of pSLE patients with PH, the prevalence of this complication approximated that of adult SLE cohorts. However, in contrast to the adult population, PH presented earlier in the course of SLE in children. Additionally, outcomes were favorable with initiation of aggressive, multi‐modal immunosuppressive therapy with no recurrences. The mortality rate was much lower than described in adult cohorts.